Densification of by-products, crop residues and other biomasses for ruminant feeding: Catalytic supplementation; Part of the ration and complementarity between resources - Moujahed, Nizar (2023)
Densification of by-products, crop residues and other biomasses for ruminant feeding: - Catalytic supplementation; - Part of the ration and complementarity between recourses.